University teaching and research in information science for development cooperation - Moreiro, José-Antonio (Anuario ThinkEPI, 2012)
The information-documentation academic sector is considered in relation to cooperation in international development. Within this framework, the most frequent contributions made by information services and the actions in which university teaching and research is involved are described. Finally, the importance of contributing to the development and modernization of distance learning for information/ documentation professionals is underlined.
Keywords: Library and information science; Development cooperation; Social commitment; Africa; Distance learning.